Multi-sensory integration for strategic behavior guidance in pediatric dentistry: A narrative review - Anshula Deshpande; Pooja Bane; Sivakumar Nuvvula (Arbu Academic Publishing, 2022)
Dental procedures, especially invasive ones, can elicit fear and anxiety. Young children are especially prone to dental anxiety as they lack the necessary coping skills. Under such circumstances, communication management and the proper use of commands are universally considered beneficial. In this narrative review, we present a compendium of communication strategies for the engagement multi-modal sense of a child in a dental operatory. Incorporatingthe visual, auditory, read &/write & kinesthetic-tactile (VARK) models in behavior guidance during dental treatment can ensure that the child has a positive dental experience. Further amplification of this model is done by incorporating it into a multi-sensory adapted dental environment. The sensory-adapted milieu can create a positive psychological impact while the dental treatment is in progress, thereby comforting the child.